Faculty Senate Recommendation to the Provost, May 2, 2005 - Salisbury University Faculty Senate (My University, 2005)
A recommendation from the Faculty Senate to the Provost on adjusting the academic calendar.
Keywords: Shared Governance; Governance Consortium